The Relationship between Parenting Patterns and Social Behavior of Adolescents in Sikabau Village, Pulau Punjung District, Dharmasraya Regency - Leska, Vingki; Natsir, MHD (Universitas Negeri Padang, 2025)
This study is based on the poor social behavior of adolescents aged 15–18 years in Nagari Sikabau, Pulau Punjung District, Dharmasraya Regency. It is estimated that poor parenting techniques are the cause. The purpose of this study is to analyze the relationship between parenting techniques used by parents and the social behavior of adolescents in Nagari Sikabau. Quantitative techniques and correlation research methodology were used in this study. A total of 70% of the population was selected from 80 participants in this study, and 56 responses were obtained using area sampling techniques. The Pearson Product Moment correlation approach was used to analyze the data collected from the questionnaire that had been through validity and reliability tests. The study's conclusions indicate that: (1) parenting practices in Nagari Sikabau, Pulau Punjung District, Dharmasraya Regency, are classified as poor; (2) the social behavior of adolescents in Nagari Sikabau, Pulau Punjung District, Dharmasraya Regency, is categorized as poor; and (3) the social behavior of adolescents in Nagari Sikabau, Pulau Punjung District, Dharmasraya Regency, has a significant correlation with parental parenting styles.